SELF-BOOK ART THERAPY SEBAGAI INTERVENSI PSIKOSOSIAL UNTUK MENGURANGI KECEMASAN PADA LANSIA PALIATIF DENGAN PENYAKIT KRONIS DI PANTI WERDA BUDI MULIA 2 CENGKARENG - Tri Setyaningsih; Ratu Chairunisa; Shinta Prawitasari; Aldi Saputra; Tiara Aulia Anisa (Community Development in Health Journal, 2025)
Introduction & Aim: Elderly individuals with chronic illnesses in palliative care often experience anxiety and limited understanding of emotional regulation. This community service program aimed to improve knowledge about anxiety management and reduce anxiety levels among elderly residents at Panti Werda Budi Mulia 2, Cengkareng, through Self-Book Art Therapy as a psychosocial intervention. Method of Activity: The program consisted of pre-test and post-test assessments, education on anxiety and mental health, and two sessions of Self-Book Art Therapy involving 30 elderly participants with chronic diseases. Knowledge levels were measured using a structured questionnaire, while anxiety levels were assessed using the Geriatric Anxiety Inventory (GAI). Results: Prior to the intervention, 40% of participants were in the low knowledge category, 50% moderate, and 10% good. After the program, 40% reached the good category and 43% achieved the very good category. The mean GAI score decreased from 14.2 (moderate anxiety) to 7.6 (low anxiety), showing a substantial reduction in anxiety levels. Discussion: Self-Book Art Therapy enhanced participants’ understanding of emotional regulation and promoted relaxation, emotional expression, and social connection. The program also empowered caregivers to continue the activity sustainably. Conclusion: Self-Book Art Therapy is an effective, low-cost psychosocial intervention that improves knowledge about anxiety management and reduces anxiety levels among elderly individuals in palliative care.